Multisensor data fusion : from algorithms and architectural design to applications / edited by Hassen Fourati ; Krzysztof Iniewski, managing editor. - Fourati, Hassen; Iniewski, Krzysztof, 1960- (Devices, circuits, and systems., 2016)
'Multisensor Data Fusion' covers the contemporary theory and practice of multisensor data fusion, from fundamental concepts to cutting-edge techniques drawn from a broad array of disciplines.